Sustainable Ecosystem Design: Biodiversity-Integrated Organic Farming System - Sarmiento Banjie G. (E3S Web of Conferences)
This study evaluated the components of small-scale lowland BIO (Biodiverse, Integrated, and Organic) farms in Bay, Laguna, Philippines. The farms are characterized by a variety of plant species, including ornamentals, perennial vegetables, annual vegetables, herbs, and medicinal plants. The study aimed to determine the cultural practices being conducted on the farms, create a resource flow diagram, identify sources of renewable energy, describe ecosystem services provided by the farms and assess the farms using SWOT analysis. The results showed that farms employ sustainable agricultural practices such as soil conditioning, crop establishment techniques, and integrated pest management (IPM) strategies. The farms also utilize circular economy principles, conserving water and soil quality while providing ecosystem services such as provisioning, regulating, supporting, and cultural. The SWOT analysis revealed that the farms’strengths include its sustainable practices, multi-functionality, and potential for agrotourism. However, its weaknesses include the lack of product development and potential threats such as climate change, crop infestation, and land conversion. The study demonstrates the importance of sustainable agriculture in achieving food security and highlights the need for policymakers to adopt sustainable intensification strategies to reduce environmental impact from food production. The findings also emphasize the importance of knowledge sharing and building among farmers to improve their skills and adapt to changing conditions.